Violence in Brazilian schools: Analysis of the effect of the #Tamojunto prevention program for bullying and physical violence. (27th December 2017) - Gusmões, Júlia D.S.P.; Sañudo, Adriana; Valente, Juliana Y.; Sanchez, Zila M.
ABSTRACT: A randomized controlled trial was conducted with 6637 7th‐ and 8th‐grade students in 72 public schools in 6 Brazilian cities to evaluate the effects of the European drug prevention program Unplugged, called #Tamojunto in Brazil. This article evaluates the effects of #Tamojunto on the prevention of bullying and physical violence. Baseline data were collected from both intervention and control groups prior to program implementation. Follow‐up data collection was performed 9 and 21 months later. Generalized estimating equations were used to evaluate changes in the reporting of receiving or practicing bullying and physical violence over time. The program was found to reduce the likelihood of receiving bullying, particularly in the stratum of girls aged 13–15 years at the 9‐month follow‐up time point. The effect was not sustained at 21 months. There was no significant effect for practicing bullying and for receiving or practicing physical violence.